A pore-scale study of transport of inertial particles by water in porous media. (2nd November 2019) - Endo Kokubun, M.A.; Muntean, A.; Radu, F.A.; Kumar, K.; Pop, I.S.; Keilegavlen, E.; Spildo, K.
Highlights: Hydrodynamic effects play a role in accumulating (inertial) particles in porous media flow. Clogging occurs when particles accumulate at the entrance of a narrow pore throat. Clogs are formed in porous media with a heterogeneous pore size distribution, but not in microscopically homogeneous media. Abstract: We study the transport of inertial particles in water flow in porous media. Our interest lies in understanding the accumulation of particles including the possibility of clogging. We propose that accumulation can be a result of hydrodynamic effects: the tortuous paths of the porous medium generate regions of dominating strain, which favour the accumulation of particles. Numerical simulations show that essentially two accumulation regimes are identified: for low and for high flow velocities. When particles accumulate at the entrance of a pore throat (high-velocity region), a clog is formed. This significantly modifies the flow, as the partial blockage of the pore causes a local redistribution of pressure, which diverts the upstream water flow into neighbouring pores. Moreover, we show that accumulation in high velocity regions occurs in heterogeneous media, but not in homogeneous media, where we refer to homogeneity with respect to the distribution of the pore throat diameters.